Effect of the clathrate complex of selenopyran and β-cyclodextrin on the rate of healing of a conditionally aseptic full-thickness planar wound in rats - D. V. Zayats; O. V. Buyklinskaya; Ju. R. Fedotova; N. S. Felenko (Разработка и регистрация лекарственных средств)
Introduction. Selenopyran is an organic selenium compound with sharply hydrophobic properties. An increase in solubility in water (and as a consequence – and bioavailability) is possible due to the formation of inclusion complexes with cyclodextrins.Aim. The aim of this work was to study the effect of a gel containing a clathrate complex of selenopyran with β-cyclodextrin on the rate of wound healing on a model of a conditionally aseptic full-thickness planar wound in rats.Materials and methods. The object of the study was a gel containing a clathrate complex of selenopyran with β-cyclodextrin (the content of selenopyran in the gel was 0.1 %). A model of a full-thickness planar wound in sexually mature male rats was used. 20 individuals were divided into 2 groups – intact (without treatment) and experimental (received gel treatment). Efficacy was assessed by the change in wound area at 3, 5, 7, 9, 11 and 14 days after application of wound.Results and discussion. The results of the study showed that the relative area of the wounds in the treated animals by the 3rd day of the experiment was less than in the intact ones. On the fifth day of the experiment, the differences were statistically significant (57.49 ± 12.51 % in treated animals versus 85.27 ± 26.61 % in intact animals). By the 14th day of the experiment, there were practically no differences in the groups of animals.Conclusion. The results obtained indicate that when using a gel containing selenopyran in combination with β-cyclodextrin, it accelerates the transition from the inflammation phase to the proliferation phase. This is most likely due to the antioxidant properties of selenopyran. Considering the lower concentration of selenopyran in comparison with the therapeutic concentrations of other antioxidants (taurine, allantoin), it can be considered as a promising wound healing agent for further study.